Social media as a criminogenic factor for the illegal sale of species in Tamaulipas (Mexico): the case of Facebook - Carpio-Domínguez, José Luis (Universidad Autónoma de Tamaulipas, 2018)
Social media platforms such as Facebook are useful tools for trade. However, the illegal sale of animals and plants, which is the third biggest illegal trade in the world, is taking advantage of this new mechanism of illegal sale and distribution of threatened or illegal species in the state of Tamaulipas mainly due to the lack of legal proceedings to prosecute violators in situ. The objective of this study was to determine the active use of Facebook as a criminogenic factor in the buying and selling of flora and fauna species that have been either listed as endangered in the Mexican Official norm NOM-059-SEMARNAT-2010 or not acquired legally and sustainably in Tamaulipas, Mexico. The digital search of the Facebook pages dedicated to the sale of species in the southern, central and northern areas of the state was carried out during the period from January to November 2016. Through a mixed retrospective method, the illegal sale of species as part of the criminodynamics of antisocial behavior that violates the collective heritage and the common good was analyzed. It was found that more than $ 176 260 were earned through illegal trade in this platform during the period under study: the Northern Zone with 96 % of the economic participation, followed by the Sout-hern Zone with 3 %, and finally the Central Zone with the 1 %. The use of a criminogenic perspective has enabled us to characterize the existing criminodynamics in the illegal trade of species through social media platforms. This knowledge can help the corresponding authorities develop legal initiatives to be able to prosecute violators. Similarly, the knowledge generated here can also be used to develop environmental education programs that can prevent the population from getting involved in either local or federal crimes.